Patients with ICD-10-CM codes for Naegleriasis in U.S. hospitals, 2016-2024: A retrospective analysis of administrative data - Thad Wilkins; Alyssa Harris; Will Cagle; Pravin Vikram; Phillip Coule; Jose Vazquez (International Journal of Infectious Diseases)
Objectives: Naegleria fowleri is a free-living amoeba that causes primary amoebic meningoencephalitis (PAM), a rare and nearly always fatal infection. Other free-living amoebae may cause similar presentations. This study characterizes demographic features, clinical outcomes, and antimicrobial use among patients coded with naegleriasis in a large administrative database. Methods: A retrospective analysis was conducted using the Vizient® Clinical Database, which includes discharge-level data from over 500 U.S. hospitals. Patients discharged between January 2016 and February 2024 with ICD-10-CM code B60.2 (naegleriasis) were identified. Demographics, inpatient mortality, antimicrobial use, and discharge disposition were summarized using descriptive statistics. Results: Twenty-two patients were identified. The mean age was 37 years; 73% were adults. In-hospital mortality was 50%. Survivors had longer hospital stays than nonsurvivors. Amphotericin B and fluconazole were the most used antimicrobials. Diagnostic confirmation of PAM was unavailable, and additional clinical details were not accessible. Conclusions: Patients coded with naegleriasis were mostly adults and had lower mortality than expected for confirmed PAM. The 50% survival rate suggests possible misclassification. These findings are hypothesis-generating and highlight the need for case-based studies with laboratory confirmation to clarify epidemiologic trends.